2016
DOI: 10.1155/2016/8069354
|View full text |Cite
|
Sign up to set email alerts
|

The Midterm Surgical Outcome of Modified Expansive Open-Door Laminoplasty

Abstract: Laminoplasty is a standard technique for treating patients with multilevel cervical spondylotic myelopathy. Modified expansive open-door laminoplasty (MEOLP) preserves the unilateral paraspinal musculature and nuchal ligament and prevents facet joint violation. The purpose of this study was to elucidate the midterm surgical outcomes of this less invasive technique. We retrospectively recruited 65 consecutive patients who underwent MEOLP at our institution in 2011 with at least 4 years of follow-up. Clinical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
3
7
0
Order By: Relevance
“…The pain subscore was already low before the operation and became even lower at 1 year post operation. Yeh et al [39] preserved the C2 and C7 muscle attachments and reported similar results with other studies. Similarly, Sakaura et al [40] performed the C3-C6 laminoplasty and reported that the postoperative axial neck pain was 5% at 1 year and 0% at the final follow-up.…”
Section: Surgical Outcomesupporting
confidence: 77%
See 4 more Smart Citations
“…The pain subscore was already low before the operation and became even lower at 1 year post operation. Yeh et al [39] preserved the C2 and C7 muscle attachments and reported similar results with other studies. Similarly, Sakaura et al [40] performed the C3-C6 laminoplasty and reported that the postoperative axial neck pain was 5% at 1 year and 0% at the final follow-up.…”
Section: Surgical Outcomesupporting
confidence: 77%
“…Several studies showed that laminoplasty reduced cervical ROM in various degrees [34,35,[37][38][39][40]. As shown in Table 2, it seems that the preservation of C2 and C7 muscle attachments have an important role in the preservation of cervical ROM postoperatively.…”
Section: Radiological Outcomementioning
confidence: 97%
See 3 more Smart Citations